Analyzing the Impact of Blended-Learning Implementation on Student Engagement and Achievement in Secondary Schools During Pandemic Recovery - M.Isa; Maria Anita Titu; Olabode Adeyinka Ayoola (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study examines the impact of blended learning on student engagement and academic achievement in secondary schools during the recovery phase of the pandemic. A quantitative research approach was employed, utilizing a comparative design to assess the differences between blended learning and conventional learning models. Data were collected through student engagement surveys and academic performance records from secondary school students exposed to both learning models. The results indicated that students in the blended learning model exhibited significantly higher levels of engagement across behavioral, emotional, and cognitive dimensions compared to those in the conventional model. Academic achievement was also notably higher in the blended learning group. Statistical analysis, including t-tests and linear regression, revealed a strong positive correlation between student engagement and academic performance. The study concluded that blended learning significantly enhances student involvement and performance, particularly when supported by adequate technological infrastructure and teacher preparedness. These findings suggest that blended learning should be integrated as a permanent strategy in post-pandemic education to support student success and engagement. The study also emphasizes the importance of continuous teacher training and technological support in maximizing the benefits of blended learning.